Accounting as a sustainable crafted technology for human exchange activities with nature: A defense of accounting continuity - Al-Adeem, Khalid Rasheed (Frontiers in Environmental Science, 2023)
The accounting literature establishes that accounting changes actively due to its adaptability to new roles and fulfilling functions that members of diverse societies needed. While accounting is a means that has assisted humans in monitoring resources and holding delegated individuals, administering such resources, accountable, it is, however, tested to account for human activities with nature. In practice, users of corporate reports need to be informed about the sustainability of firms in which they invest. Inquiring about sustainability is understudied and experienced low voluntary disclosure. Since reporting sustainability embraces financial and nonfinancial disclosure, this study brings to attention the enterprise concept that best fits the conceptualization of accounting at the current time, enabling the accounting profession to meet the urging ecological, environmental, and social needs of society from reporting entities, primarily entities whose beneficiaries are part of society. Accounting is the only tool business possesses to monitor its internal affairs, administer its external relations, and assess the performance of the business. Adopting the enterprise theory enables accounting to continue its superiority as a device that meets the emerging needs of business and society. In this regard, accounting is a sustainable profession because it maintains its existence by assisting corporations in meeting the obligations that they owe toward members of their society to report the impact of its actions on members of society at large.